Business communication: Basic concepts and skills - Parikh, J. P. author; Surve, A. (Anshu); Swarnabharati; Bahrainwala, A. (Asma) (Hyderabad: Orient BlackSwan, 2011)
This book deals with the basic concepts and practices of communication and their applications in the business world today. The present-day global market demands employment ready graduates with good communication skills. This book will help prepare students to meet this important requirement for jobs in the corporate world by equipping them with the necessary knowledge and technical knowhow. The useful range of topics it covers makes Business Communication: Basic Concepts and Skills a comprehensive textbook for students of business communication.
Keywords: Business communication; English communication